Thermochemical Recycling of Solid Biomass Materials for Achieving Sustainable Goal: A Complete Characterization Study on Liquid Yield Products - Ashok Kumar Koshariya; J. Madhusudhanan; Harishchander Anandaram; J. Isaac JoshuaRamesh Lalvani; L. Natrayan; Praveen Bhai Patel; P. Jayaraman; Ezhakudiyan Ravindran; Palanisamy Rajkumar (Journal of Chemistry)
In order to achieve sustainability goals, biomass is a renewable energy source that lowers emissions of greenhouse gases and other hazardous gases. Biochemical and thermochemical methods are both used to produce bioenergy from biomass. Pyrolysis is an effective thermochemical conversion technique used for the conversion of biomass into energy-rich bio-oil. In this study, the pyrolysis characteristics and bio-oil obtained from the residues of Ricinus communis were investigated. The experimental run was designed to analyze the impact of bed temperature on product yield by varying the process temperature from 350°C to 750°C. In this study, a maximum of 46.5 wt% of bio-oil was produced at 500°C. The maximum conversion was recorded at temperatures ranging from 450°C to 550°C. The bio-oil obtained at maximum yield conditions was analyzed using different analytical techniques. The Fourier transform infrared spectroscopy (FT-IR) and gas chromatography and mass spectroscopy (GC-MS) analyses of the bio-oil revealed that the oil has a significant amount of phenol derivatives, oxygenated chemicals, acids, and esters. The physical properties of the bio-oil showed that it is viscous and has a medium heating value compared with commercial fossil fuel.